The Answer Social Challenges: Social Accounting and Social Accounting Measurement - Arisandi Dwiharto; Erma Sofriana Irmaningsih; Lenny Christina Nawangsari; Sigmin Johanes Lo; Veithzal Rivai Zainal (International Journal of Social Service and Research (IJSSR), 2023)
The main purpose of this accounting is to increase the awareness and attention of companies to the impact of their activities on the environment. Social accounting can also be a bridge between companies and non-profit organizations related to the environment. The methodology used is qualitatively using review literature on the definition of social accounting and how to measure social accounting in the process of its implementation to answer the social challenge that this social accounting audit is the answer to the license to operate for a company or non-profit organization which we often know as Corporate Social Responsibility (CSR). The result is (1) CSR management requires companies to implement environmental protection and economic development responsibilities, so they will take the initiative to create environmental-related knowledge to adapt to changing external ecological requirements and use green technology to build market forces. (2) Some of these sustainability reporting standards must be made by the company so that in the reporting process not only financial statements but also sustainability reports are presented in the portfolio is shared publicly as an indicator of the company's commitment to the implementation of sustainability programs, where this sustainability report must be approved by a licensed certified person. (3) With the spirit of social-techno-entrepreneurship as a form of integration of all components, a company cannot separate between economic and social values, so that the interests of various parties can be accommodated simultaneously. Researchers suggest that companies must be able to present economic legitimacy (creation of job opportunities), social legitimacy (improvement of welfare), trust in interaction (corporate response defines problems in society and mutual interaction in common life into a form of License to Operate for companies or non-profit organizations.